Strategi Dakwah Mualaf Center Indonesia Peduli (MCIP) Medan dalam Penguatan Akidah dan Identitas Keislaman Mualaf - Hamdani Pratama; Zulkarnain Abdurrahman (Institut Agama Islam Negeri (IAIN) Curup, 2025)
The process of changing beliefs for a convert to Islam is often accompanied by various challenges, both psychological, social and theological. This research aims to analyze the da'wah strategies implemented by MCIP Medan in guiding and strengthening the Islamic understanding of converts. The research method used is qualitative with a descriptive approach. Data was obtained through observation, interviews and documentation studies. The research results show that MCIP Medan implements a da'wah strategy based on education, personal assistance, and community strengthening. Education is carried out through structured Islamic studies, while personal assistance involves mentoring individuals to help converts face the challenges they experience. Apart from that, community strengthening is carried out by forming social networks that support the continuity of the faith of converts. With this strategy, MCIP Medan is able to have a significant impact in building the faith and Islamic identity of converts.